Amivantamab (JNJ-61186372) induces clinical, biochemical, molecular, and radiographic response in a treatment-refractory NSCLC patient harboring amplified triple EGFR mutations (L858R/ T790M/G796S) in cis. (February 2022) - Nagasaka, Misako; Balmanoukian, Ani S.; Madison, Russell; Zhang, Shannon S.; Klempner, Samuel J.; Ou, Sai-Hong Ignatius
Highlights: First detaled patient case report of amivantamab monotherapy active against EGFR triple mutation (L858R/T790M/G796S) in cis . Symptomatic, biochemical, and molecular response were rapid after initiation of amivantamab. Antibody therapy may be successfully against on-target EGFR TKI resistance regardless of the underlying resistance mutations. Abstract: The sequential use of 1 st -/2 nd -generation to 3 rd -generation epidermal growth factor (EGFR) tyrosine kinase inhibitors (TKIs) has led to the emergence of triple EGFR mutations generally consisting of the founder mutation (del 19 or L858R), gatekeeper mutation (T790M) and mutation (C797S) that abolishes the covalent binding of osimertinib to the EGFR protein (i.e., del 19 or L858R/T790M/C797S). Besides C797S, other tertiary mutations confer structural steric hindrance to osimertinib rather than preventing its covalent binding to the EGFR kinase domain such as solvent front mutation (G796S) or others such as L792F/H mutation. "Fourth-generation" EGFR TKIs are being developed to inhibit these triple mutations, in particular, in the background of compound T790M/C797S mutations but they are still in early clinical stages of development. Amivantamab, a bi-specific EGFR/MET monoclonal antibody that can affect Fc mediated trogocytosis of the EGFR protein has been approved for the treatment of EGFR exon20 insertion mutations and has demonstrated activity against a myriad of compound EGFR mutations. Here we report amivantamab monotherapy induced symptomatic, biochemical, molecular, and radiographic responses in a NSCLC patient with triple EGFR mutations in cis in the background of EGFR amplification.